Unstable total hip replacement: why? Clinical and radiological aspects. Issue 2 (December 2020) - Perticarini, Loris; Rossi, Stefano M P; Benazzo, Francesco
Introduction: Dislocation after total hip arthroplasty (THA) is the most common cause of revision hip surgery in the United States, ahead of aseptic loosening and infection, and is responsible for considerable economic cost related to frequent readmission and/or revision surgery. The aim of this article is to identify the clinical and radiological factors related to the unstable total hip replacement. Methods: We performed a literature search to assess current strategies to define clinical and radiological characteristics of dislocation after primary THA using the PubMed platform. The characteristics related to THA instability were divided into patient related factors, implant related factors and surgeon experience. Results: Patient-related factors for instability identified are: age; inflammatory joint disease; prior hip surgery; preoperative diagnosis; comorbidity; ASA score; presence of spino-pelvic abnormality; and neurological disability. Gender, simultaneous bilateral THA and restrictive postoperative precautions do not influence rate of THA dislocation. Implant related factors identified are: surgical approach; component malposition; femoral head size; and the use of dual-mobility or constrained solution. Surgeon experience also reduces the rate of dislocation. Discussion: Dislocation is a major complication of THAs, and causes include patient-derived factors, surgical factors, or both. It is imperative to determine the cause of the instability via a complete patient and radiographic evaluation and to adjust the reconstruction strategy accordingly.